Convergence of the German Bundesländer: Lessons for the EU - Michael C. Burda (Intereconomics, 2019)
Evaluating real convergence or divergence in the EU is challenging because it is diffi cult to fi nd an appropriate counterfactual or comparison benchmark, or to formulate one. Should we compare the status quo with convergence that would have been obtained had the European Union (EU) never existed? Or under different monetary arrangements - fl exible or fi xed exchange rates, or a monetary union? With or without deep trade integration, or factor mobility as in the United States? I will exploit recent research and discuss real convergence in the EU, using the new and old German Bundesländer (states) since reunifi cation as a foil for the integration process. German unifi cation provides an excellent laboratory: an economy populated by Europeans with labour and capital mobility unimpeded by national boundaries, trade barriers, or culture, tradition and institutions after 1990.
Keywords: 330; Economic convergence; Germany; Investment; Productivity; Regional policy